NEGOTIATING IN FINNISH GROCERY RETAIL - Negotiation Narratives of S-group, Kesko and Lidl - Monthan, Heikki (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
In this research retail negotiations are explored through the question: What characteristics are distinctive to negotiating in Finnish grocery retail trade? To shed light on the research question I interviewed experienced retail negotiators and mapped out the most important characteristics of the retail negotiations. I described through examples the most prominent challenges negotiators face in their negotiations and elaborated what kind of tools the experienced negotiators use to overcome those challenges. The research results add up to a groundwork frame for retail negotiations with which further research can be more easily directed to any area of interest in the Finnish grocery retail negotiations. The framework can give ideas or frames for further research, or function as a general guideline of factors to consider when negotiating in Finnish retail field. The results were divided into 3 sections: Characteristics, Challenges and Tools. Different negotiation models help negotiators and researchers understand negotiation dynamics. This research adds to that pool by focusing on elements essential to consider specifically in the context of Finnish retail. Finland offered an exceptionally interesting setting to study negotiation, as grocery retail trade in Finland is highly centralized. Especially for those interested understanding a centralized setting such as Finland’s retail field, the framework presented in this research might provide a valuable spectrum of essential negotiation elements. Learning is a lifelong process, but that path can be evened by tuning in on what others have learned during their own endeavors in similar situations. Seasoned negotiators have many stories to tell about negotiating that can be drawn upon and by doing so, we can avoid having to spend time learning the same insights twice. This research drew on narrative, case-research and interviewing to find out how seasoned negotiators in the field of Finnish retail experienced negotiation, what challenges negotiations pose and what tools can be used to overcome them

Tutkimus tarkastelee kaupan alan neuvotteluja analysoimalla, mitkä ominaispiirteet ovat tunnusomaisia Suomen päivittäistavarakaupan liikeneuvotteluille. Tutkimuskysymyksen selvittämiseksi haastattelin kokeneita päivittäistavarakaupan neuvottelijoita ja kartoitin keskeisimmät alan neuvotteluiden luonteenpiirteet. Tutkimuksessa tarkastellaan yleisimpiä neuvottelujen haasteita, ja selvitetään, mitä työkaluja kokeneet neuvottelijat käyttävät selvitäkseen niistä haasteista. Tulokset muodostavat viitekehyksen päivittäistavarakauppaneuvotteluille, jonka avulla tulevaa tutkimusta voidaan helpommin suunnata mille tahansa neuvottelujen osa-alueelle. Kehikko voi antaa ideoita tulevalle tutkimukselle, tai toimia yleisenä lähtökohtana ja olennaisten muuttujien raameina päivittäistavarakaupassa neuvotteleville. Tulokset jakautuvat kolmeen osioon: Ominaispiirteet, Haasteet ja Työkalut. Erilaiset neuvottelumallit auttavat neuvottelijoita ja tutkijoita ymmärtämään neuvotteluiden vaikutussuhteita. Tutkimus on osaltaan lisä neuvottelukirjallisuuteen ja paneutuu osa-alueisiin, jotka ovat erityisen olennaisia juuri Suomen päivittäistavarakaupan asiayhteyksissä. Suomen markkinoiden keskittyneisyys tuo neuvotteluille omat ominaispiirteensä, joita tutkimus tarkastelee neuvottelujen näkökulmasta. Toimialan kokeneiden neuvottelijoiden tarinat muodostavat tutkimuksen rungon, ja niitä analysoimalla aiheesta kiinnostuneet voivat pohtia neuvotteluja uudessa valossa. Tutkielmassa käytettiin narratiivista tutkimusta, tapaustutkimusta sekä haastatteluja selvittämään, kuinka kokeneet neuvottelijat Suomen päivittäistavarakaupan alalla kokevat neuvottelemisen, mitä haasteita neuvotteluihin kuuluu sekä mitä työkaluja voidaan käyttää niiden voittamiseksi.